1960
DOI: 10.1042/bj0740279
|View full text |Cite
|
Sign up to set email alerts
|

The purification of human caeruloplasmin

Abstract: SYNTHESIS OF PROTEIN AND RIBONUCLEIC ACID 279 results do not, however, exclude the possibility that there might be coupling between the synthesis of certain proteins and the synthesis of some particular fraction of the ribonucleic acid. Whether protein synthesis can be suppressed without affecting RNA synthesis remains undecided, since the amino acid analogue, somewhat paradoxically, inhibited RNA synthesis much more readily than protein synthesis. Both thienylalanine and azaguanine suppressed cytoplasmic RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0
2

Year Published

1960
1960
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(33 citation statements)
references
References 17 publications
2
29
0
2
Order By: Relevance
“…A preliminary report on part of this work has appeared (Curzon, 1965a Broman et al (1963) and Morell, 1957;Curzon & Vallet, 1960;Deutsch, Kasper & Walsh, 1962 NN-Dimethyl-p-phenylenediamine sulphate. This compound was obtained from Kodak Ltd. and purified by dissolving it in methanol containing a little 5% SO2, removing the insoluble residue byffltration and precipitating the compound with ether.…”
mentioning
confidence: 99%
“…A preliminary report on part of this work has appeared (Curzon, 1965a Broman et al (1963) and Morell, 1957;Curzon & Vallet, 1960;Deutsch, Kasper & Walsh, 1962 NN-Dimethyl-p-phenylenediamine sulphate. This compound was obtained from Kodak Ltd. and purified by dissolving it in methanol containing a little 5% SO2, removing the insoluble residue byffltration and precipitating the compound with ether.…”
mentioning
confidence: 99%
“…pH 5.2 ve 37°C koşullarında asetat tamponunda hazırlanan P-fenilen diamin diklorid (PPD) serum örnekleri ile oluşan renkli ürünün absorbansı spektrometrede 550 nm'de okunarak serum seruloplazmin ölçümleri incelendi [14] .…”
Section: öRneklerin Analiziunclassified
“…It was also rapidly oxidized by the gill plate enzyme, at about the same rate as 5-hydroxytryptamine. It is known that 5-hydroxyindoleacetic acid is oxidized by human caeruloplasmin (Curzon and Vallet, 1960).…”
Section: Substrate Specificitymentioning
confidence: 99%
“…Erspamer (1955) has shown that in man and dog less than one-half of the amine administered is excreted as 5-hydroxyindoleacetic acid in the urine, and he has found that in a number of herbivorous species the urine contains only insignificant amounts of 5-hydroxyindoleacetic acid. It is not known to what extent this deficit is accounted for by known metabolites of 5-hydroxytryptamine, for example, the 0-glucuronate and the O-sulphate, the N-acetyl derivative or 5-hydroxyindoleaceturic acid (Curzon, 1957;Chadwick and Wilkinson, 1958;McIsaac and Page, 1959).…”
mentioning
confidence: 99%
See 1 more Smart Citation